(untitled) (Research, Society and Development, 2021)
The objective of this study was to analyze the impacts caused by sleep disorders on the quality of life of nursing professionals. To this end, a descriptive, quantitative research was carried out with 40 nursing professionals working in intensive care units in a public hospital in Teresina-PI, from February to April 2021. The questionnaires used were the Pittsburgh Sleep Quality Index and The World Health Organization Quality Of Life-Bref, via google forms. The collected data were stored in Microsoft Excel 2010 spreadsheets and analyzed with the Statistical Package of Social Science version 20.0. As a result, the components of the sleep questionnaire most affected were: subjective quality, latency, duration and dysfunction during the day. Poor sleep quality was observed in 95% of the participants, with insomnia being presented in 13%. As for the quality of life questionnaire, 50% rated it as good and 40% were dissatisfied with their health. The scores for each domain were transformed into a scale of 0-100; higher averages suggested better quality of life. The most compromised domain was the environment (related to the domestic environment, financial resources, leisure and the environment). The most affected facets were: sleep and rest, positive feelings, sexual activity, recreation and leisure. Thus, it was found that a large part of the sample suffers or has already suffered from sleep disorders. Thus, sleep quality is a factor that affects quality of life.